2021
DOI: 10.1002/lt.26091
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Vascular Resistance Predicts Mortality and Graft Failure in Transplantation Patients With Portopulmonary Hypertension

Abstract: Earn MOC for this article: www.wileyhealthlearning.com/aasld.aspx Portopulmonary hypertension (POPH) is a pulmonary vascular disease associated with significant morbidity and mortality in those with liver disease, conferring a higher mortality in patients awaiting liver transplantation (LT). Although not a transplant indication, patients with POPH can experience significant clinical improvement following LT, and those maintaining a mean pulmonary artery pressure (MPAP) <35mm Hg and a pulmonary vascular resista… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 35 publications
0
18
0
Order By: Relevance
“…Because of the limitations of current study population, possibilities of impaired ion channels cannot be completely excluded (11). Pulmonary arterial hypertension has been shown to be involved in liver fibrosis at the gene level and confers higher mortality (36)(37)(38). Cardiac dysfunction was first attributed to the direct effect of alcohol; however, it was revealed to be independent of the etiology (39, 40).…”
Section: Discussionmentioning
confidence: 99%
“…Because of the limitations of current study population, possibilities of impaired ion channels cannot be completely excluded (11). Pulmonary arterial hypertension has been shown to be involved in liver fibrosis at the gene level and confers higher mortality (36)(37)(38). Cardiac dysfunction was first attributed to the direct effect of alcohol; however, it was revealed to be independent of the etiology (39, 40).…”
Section: Discussionmentioning
confidence: 99%
“…We chose PVR to conduct the correlation analysis not only because of the two-time fold change between POPH and IPAH but also because PVR could predict mortality and graft failure in transplantation patients with POPH [ 24 ]. Although total bilirubin and direct bilirubin were positively correlated with PVR, the independent predictor of PVR elevation was NT-proBNP in the IPAH group.…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective cohort study of the OPTN database found that a pre‐LT PVR of ≥1.6 WU was associated with an increased risk of post‐LT mortality, but because of the limitations of the database, there were no data regarding RV function or other important prognostic parameters. [ 21 ] A PVR <1.6 WU, or 128 dynes‐s‐cm −5 , is also not a realistic treatment goal for most patients with POPH. Currently, there is insufficient evidence to further modify MELD exception criteria regarding the PVR threshold, but additional research is needed to guide decisions and optimize posttransplant outcomes.…”
Section: The Futurementioning
confidence: 99%